Structuring healthcare advance directives: Evidence from Chinese end‐of‐life cancer patients' treatment preferences - Zi‐Meng Ye; Ben Ma; Elizabeth Maitland; Stephen Nicholas; Jian Wang; An‐Li Leng (Wiley, 2023)
Abstract Background Patients' treatment decisions may be influenced by the ways in which treatment options are presented. There is little evidence on how patients with advanced cancer choose preferences for advance directives (ADs) in China. Informed by behavioural economics, we assess whether end‐of‐life (EOL) cancer patients held deep‐seated preferences for their health care and whether default options and order effects influenced their decision‐making. Methods We collected data on 179 advanced cancer patients who were randomly assigned to complete one of the four types of ADs: comfort‐oriented care (CC) AD (comfort default AD); a life extension (LE)‐oriented care option (LE default AD); CC (standard CC AD) and LE‐oriented (standard LE AD). Analysis of variance test was used. Results In terms of the general goal of care, 32.6% of patients in the comfort default AD group retained the comfort‐oriented choice, twice as many as in the standard CC group without default options. Order effect was significant in only two individual‐specific palliative care choices. Most patients (65.9%) appointed their children to make EOL care decisions, but patients choosing the CC goal were twice as likely to ask their family members to adhere to their choices than patients who chose the LE goal. Conclusion Patients with advanced cancer did not hold deep‐seated preferences for EOL care. Default options shaped decisions between CC and LE‐oriented care. Order effect only shaped decisions in some specific treatment targets. The structure of ADs matters and influence different treatment outcomes, including the role of palliative care. Patient or Public Contribution Between August and November 2018, from 640 cancer hospital medical records fitting the selection criteria at a 3A level hospital in Shandong Province, we randomly selected 188 terminal EOL advanced cancer patients using a random generator programme to ensure all eligible patients had an equal chance of selection. Each respondent completes one of the four AD surveys. While respondents might require support in making their healthcare choices, they were informed about the purpose of our research study, and that their survey choices would not affect their actual treatment plan. Patients who did not agree to participate were not surveyed.